Conductive adhesive composition for secondary battery and application thereof

By using a conductive adhesive composition with suitable rheological characteristics, the problem of single-wall carbon nanotubes being easily agglomerated and unevenly distributed in the negative electrode slurry of lithium-ion batteries is solved, and the circulation performance and pole processing of lithium-ion batteries are improved. stability.

CN118755419BActive Publication Date: 2024-12-17JIANGSU YITE NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411240133.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-17
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

During the preparation of negative electrode slurry for lithium-ion batteries, single-wall carbon nanotubes are prone to agglomeration and uneven distribution, resulting in poor cell circulation performance, low peel strength and high electrode sheet resistance.

Method used

The conductive adhesive composition with rheological characteristics conforming to a certain range is adopted, including solvents, polymers and conductive agents, and a stable system is formed through free radical polymerization to avoid agglomeration and gels, and the processing stability and conductivity of the electrode sheet are improved.

Benefits of technology

The stability and uniformity of the negative electrode slurry are achieved, the peel strength and circulation performance of the electrode sheet are improved, and the resistance of the electrode sheet is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a conductive adhesive composition for secondary batteries, which improves the problem of conductive agents, especially single-walled carbon tubes, being easy to agglomerate during the negative electrode homogenization process, and the problem of easy gelation during the negative electrode homogenization and coating process, thereby obtaining a stable, uniform secondary battery electrode with lower electrode resistance and higher peel strength, and improving the battery cycle performance. The conductive adhesive composition for secondary batteries of the present invention contains a solvent, a polymer and a conductive agent, and its rheological properties meet a certain range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a binder for a lithium ion battery, a lithium ion battery electrode sheet and a lithium ion battery, and belongs to the technical field of lithium ion batteries. Background Art

[0002] As the most ideal mobile power source, lithium-ion batteries have incomparable advantages over other batteries, such as high energy density, small size, long life, and no pollution. They are widely used in electric vehicles, aerospace, communications, and various portable electrical appliances.

[0003] Lithium-ion batteries are mainly composed of electrode sheets (including positive and negative electrodes), separators and electrolytes; electrode sheets are composed of electrode active materials, binders, conductive agents and current collectors. The function of the binder is to bond the active materials, conductive agents and current collectors together. Although the binder has a lower specific gravity in the electrode material, it can play a role in structural stability and therefore can have a significant impact on the battery's cycle performance.

[0004] The preparation of electrode sheets usually involves mixing and grinding the electrode active material, binder, and conductive agent evenly to prepare the negative electrode slurry, which is then coated on the current collector and processed by drying, rolling, and other processes.

[0005] Single-walled carbon nanotubes, in theory, refer to single-layer tubular structures composed of single-layer graphene structures. They have extremely high aspect ratios and excellent electrical and mechanical properties, and have good application prospects in lithium-ion battery conductive additives. At present, the commonly used single-walled carbon nanotube conductive agent is the CMC aqueous dispersion of single-walled carbon tubes. During the homogenization process of the negative electrode slurry, the conductive agent and the binder are added separately, but the CMC aqueous dispersion of single-walled carbon tubes often causes carbon tube precipitation and agglomeration during the homogenization process of the negative electrode slurry. In addition, since the CMC aqueous dispersion of single-walled carbon tubes and the binder are two systems, which are added separately, agglomeration and gelation are prone to occur during the preparation and coating of the negative electrode slurry, resulting in poor coating consistency, low peel strength, uneven distribution of the conductive agent, and high electrode sheet resistance, which leads to poor battery cycle performance. Summary of the invention

[0006] The problems to be solved by the invention are: first, the conductive agent, especially the single-walled carbon tube, is easy to agglomerate during the negative electrode homogenization process; second, the negative electrode is easy to gel during homogenization and coating; third, the battery cycle performance is poor due to the uneven distribution and dispersion of the single-walled carbon tube. Therefore, in the prior art, it is urgent to improve the stability of the binder and the conductive agent, improve the peel strength, and reduce the electrode sheet resistance, thereby improving the battery cycle performance.

[0007] Therefore, the purpose of the present invention is to provide a conductive adhesive composition for secondary batteries, which can maintain a stable and uniform state during the negative electrode slurry process, improve the defects of easy agglomeration and uneven distribution of the conductive agent when used alone, thereby obtaining a stable, uniform, lower electrode resistance, and higher peel strength secondary battery electrode, thereby improving the battery cycle performance.

[0008] Solution to the problem: The inventors have found through a large number of experiments, tests and comparisons that if a conductive adhesive composition with rheological properties within a certain range is used, the composition can form a stable system that is not easy to agglomerate or gel. Using the composition as a raw material for negative electrode slurry can effectively improve the convenience and stability of battery pole sheet processing, thereby effectively improving battery cycle performance.

[0009] The object of the present invention is achieved through the following technical scheme: a conductive adhesive composition for a secondary battery, comprising a solvent, a polymer and a conductive agent; the rheological properties of the conductive adhesive composition for a secondary battery are: at 25°C, the shear rate is 0.2S -1 When the apparent viscosity is 30000-100000mPa·S; the shear rate is 0.6S -1 When the apparent viscosity is 20000-50000mPa·S; the shear rate is 1.1S -1 When the apparent viscosity is 15000-40000 mPa·S. The conductive adhesive composition for secondary batteries with rheological properties in the above range, as an adhesive with conductive function, can show good leveling performance when the negative electrode slurry is coated on the electrode sheet because it is not easy to agglomerate or gel during processing. The slurry layer thickness consistency on the surface of the electrode sheet is good; after the slurry is coated, it can restore to a high viscosity state, so that the slurry is stable on the electrode sheet, thereby improving the peel strength; the conductive agent is evenly distributed in the system, effectively reducing the electrode sheet resistance, thereby effectively improving the battery cycle performance. The conductive adhesive composition for secondary batteries described in the present invention, the polymer monomer of the polymer is selected from acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, butyl methacrylate, allyl methacrylate, glycidyl methacrylate, diallyl adipate, acrylamide, methacrylamide, N-hydroxymethyl acrylamide, methylenebisacrylamide, divinylbenzene, styrene, acrylonitrile, methacrylonitrile, sodium allyl sulfonate, sodium allyl sulfonate, vinyl pyrrolidone, and any one or more combinations thereof.

[0010] In the present invention, the apparent viscosity at different shear rates in the rheological properties is measured by the method described in the examples of the present invention.

[0011] After a large number of experiments, the inventors found that the polymer formed by free radical polymerization of the monomer has more excellent anti-agglomeration and anti-gel properties, making the conductive adhesive composition for secondary batteries more stable during pole piece processing.

[0012] In the conductive adhesive composition for secondary batteries of the present invention, the polymer is prepared by free radical polymerization of polymer monomers.

[0013] The conductive adhesive composition for secondary batteries described in the present invention, the polymer contains 30% by weight or more and 85% by weight of acrylic acid (ester) monomer units. The acrylic acid (ester) monomer refers to: a polymer containing acrylic acid or / and acrylic acid structure. The use of a polymer containing 30% by weight or more and 85% by weight of acrylic acid (ester) monomer units can further improve the leveling performance of the composition, so that the thickness consistency of the slurry layer on the surface of the pole piece is good.

[0014] The conductive adhesive composition for secondary batteries described in the present invention comprises 80-100 parts of water and 0-20 parts of an organic solvent in terms of weight ratio, and the organic solvent is selected from a combination of one or more of ethanol, isopropanol, n-butanol, and acetonitrile. The high-polarity solvent allows the polymer to have better solubility in the solvent and better uniformity of the composition.

[0015] The conductive adhesive composition for secondary batteries described in the present invention, the polymer is preferably a polymer with an average molecular weight of 200,000 to 1,000,000. The polymer average molecular weight of 200,000 to 1,000,000 can further improve the leveling property and provide electrode coating stability.

[0016] The conductive binder composition for secondary batteries described in the present invention is a composite of one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, carbon black, graphite, carbon fiber, and carbon nanofibers. The conductive agent is directly added to the binder, avoiding the use of conventional suspension dispersants such as CMC commonly used for conductive agents, and enables the slurry to have both conductivity and suspension dispersibility, thereby improving the conductivity of the electrode material and the stability of the negative electrode slurry.

[0017] The conductive agent of the conductive binder composition for secondary batteries described in the present invention is preferably single-walled carbon nanotubes. Single-walled carbon nanotubes are used as the conductive agent because they have a high aspect ratio, high conductivity, and a low percolation threshold, and can be evenly and well dispersed in the binder composition, thereby maintaining optimal conductive properties while ensuring the stability of the slurry.

[0018] The conductive adhesive composition for secondary batteries described in the present invention, the polymer and the conductive agent are subjected to an in-situ polymerization process to form a conductive polymer. After the in-situ polymerization, the conductive agent can be used as a skeleton to form a comb-like structure with the polymer, so that the conductive agent has better dispersibility in the polymer, improves the stability of the conductive adhesive composition for secondary batteries, and thus improves the battery cycle performance. And the surface of the conductive agent is treated in a non-covalent functionalized form, which has no effect on the internal space electronic structure of the conductive agent, and can retain the excellent conductivity of the conductive agent.

[0019] The lithium ion battery negative electrode slurry described in the present invention comprises an electrode active material and any one of the above-mentioned conductive binder compositions for secondary batteries.

[0020] The negative electrode sheet for lithium ion secondary battery described in the present invention is prepared by coating the negative electrode slurry for lithium ion battery described above on a current collector.

[0021] The lithium ion secondary battery of the present invention comprises the negative electrode sheet for lithium ion secondary battery.

[0022] The beneficial effects of the present invention are as follows:

[0023] By using a conductive adhesive composition for a secondary battery whose rheological properties meet a certain range, the composition can form a stable system that is not easy to agglomerate or gel, has good leveling properties, has good system stability, and improves peel strength.

[0024] The negative electrode sheet prepared by using the negative electrode slurry can effectively reduce the resistance of the electrode sheet because the conductive agent is not easy to agglomerate in the slurry and is evenly and stably distributed.

[0025] The negative electrode slurry prepared using the composition avoids the use of the traditional single-walled carbon tube CMC aqueous dispersion as a conductive agent, and no longer needs to be added as two separate systems in the process of preparing the slurry. The conductive agent and the binder in the conductive binder composition for secondary batteries of the present invention can form a stable and uniform system, which significantly increases the convenience of electrode processing.

[0026] The lithium-ion secondary battery prepared by using the negative electrode sheet can effectively improve the cycle performance of the secondary battery because the negative electrode slurry on the negative electrode sheet is uniform and stable, the electrode sheet resistance is low, and the peeling strength is high. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is clearly and completely described below through specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In the embodiments and comparative examples, the test methods for the rheological properties of the binder composition, the weight percentage of the acrylic ester monomer unit in the polymer, the average molecular weight of the polymer, the leveling performance of the binder composition after coating, the peel strength of the negative electrode coating, and the cycle performance of the secondary battery are as follows:

[0029]

Polymer preparation

[0030] Add the polymer monomer and the solvent to the reactor in sequence, start stirring and heating, and raise the temperature to 60-80°C. Dissolve the initiator in the solvent to prepare the initiator solution. After the preparation is completed, mix the initiator solution and the desired copolymerized polymer monomer and then drop it into the reactor, and control the reaction temperature to 70-90°C. After the dropwise addition is completed, keep the temperature for 5-10 hours to prepare the polymer.

[0031] [Preparation of conductive adhesive composition for secondary batteries]

[0032] The solvent, the prepared polymer and the conductive agent are sequentially added into the dispersion tank, the system temperature is controlled within 25°C-50°C, dispersed for 30-80 minutes, and then dispersed for 25-30 times with a high-pressure homogenizer until the dispersion is uniform, and an in-situ polymerization reaction is carried out. The pH is adjusted to 5.5-6.5, and the solvent is added to dilute to a carbon tube concentration of 0.2%, and dispersed again for 30-80 minutes. Another batch of prepared polymers and solvents are added, and the system temperature is maintained within 40-80°C. The temperature is kept for 4-8 hours, the pH is adjusted to 7-8, and after filtering the insoluble matter, a conductive adhesive composition for a secondary battery is obtained.

[0033] [Rheological properties of adhesive composition]

[0034] The test method for apparent viscosity is as follows:

[0035] The test was performed using an MCR 92 rheometer with a constant test temperature of 25°C and a rotor model of CC39. The test method was selected as shear rheology measurement and the shear rate was set to 0.1~100S. -1 , 50 data points. Add 20mL of sample each time and place it on the test plate. Click the measurement position button to lower the measuring head to the scraping position. Scrape off excess sample and lower it to the measurement position. Wait for the temperature to reach equilibrium, perform testing and data collection, and read the shear rate as 0.2S -1 The apparent viscosity at a shear rate of 0.6S -1 The apparent viscosity and shear rate are 1.1S -1 The apparent viscosity at .

[0036] [Weight percentage of acrylic acid (ester) monomer units in polymer]

[0037] The weight percentage of acrylic acid (ester) monomer units in the polymer = the mass of acrylic acid (ester) monomers in the polymer / the mass of all monomers in the polymer

[0038] [Polymer average molecular weight]

[0039] Test instruments:

[0040] Pump: Agilent HPLC1260iso Pump G1310B

[0041] Autosampler: Agilent HPLC 1260 ALS G1329B

[0042] Column: Waters Ultrahydrogel 300x7.8mm 500-250-120A

[0043] Column box: Agilent HPLC 1260 TCC G1316A

[0044] Detector: Agilent RID G1362A

[0045] Test method: including (1) calibration, (2) sample pretreatment and (3) sample testing

[0046] Correction:

[0047] Prepare 5 to 10 calibration standard solutions with different average molecular weights using the mobile phase as solvent, with a mass concentration of 1.0 g / L. Slightly shake, and then let it stand for more than 12 hours to fully dissolve, and avoid using ultrasound, heating, etc. to accelerate dissolution.

[0048] Set the column temperature to 30°C and the mobile phase flow rate to 0.5 mL / min~1.2 mL / min, and flush the column with the mobile phase until the baseline is stable.

[0049] Use an automatic sampler to inject the calibration standard solution, and the data acquisition and processing system records the retention time of the corresponding peak of each standard sample.

[0050] Establish a calibration curve, repeat operation c three times or more, calculate the average retention time of each standard sample, and use the average retention time of each standard sample to logM i Draw a graph and perform a linear fit, with the linear correlation coefficient R not less than 0.9995. When the R value does not meet the requirements, repeat the calibration steps for the standard sample that causes the poor calibration. The poor calibration point can be found by calculating the difference between the actual average molecular weight and the average molecular weight calculated using the polynomial of the best fit line.

[0051] Sample pretreatment

[0052] Take 2g~5g of the sample and adjust the pH value to 7~9 with sodium hydroxide solution. Place it in a vacuum drying oven and dry it to a constant weight at a vacuum degree of 0.1MPa and (74±2)℃.

[0053] Sample test: Take the dried sample from (2) and prepare a sample solution. Use the same chromatographic conditions as (1) for sample analysis. The operating steps are the same as (1) c.

[0054] [Negative electrode coating peel strength]

[0055] The peel strength is measured by tensile tester method:

[0056] Cut the coated negative electrode sheet into 30mm*70mm test pieces, stick 3M's pressure-sensitive 3M-VHB double-sided tape on the side of the test piece coated with the negative electrode slurry, and stick the other side of the double-sided tape on the stainless steel plate. Fix the stainless steel plate and the test piece on the fixture of the tensile tester, and perform a 180-degree peel test at a speed of 50mm / min. The force detected when the aluminum current collector is completely peeled off is the peeling force. Peel strength = peeling force / spline width

[0057] Excellent: Peel force>9 N / m

[0058] Good: Peel force 8-9 N / m

[0059] Normal: Peel force is 7-8 N / m

[0060] Poor: Peel force <7N / m

[0061]

Negative electrode sheet resistance test

[0062] The resistivity of the negative electrode sheet is tested using a film resistor:

[0063] Cut the prepared negative electrode sheet into 60mm*80mm test pieces, measure the thickness of the electrode sheet with a micrometer, and then test it with a film resistance meter. The test head diameter is 10mm, the test pressure is 7MPa, input the electrode sheet thickness, take the four corners and the center of the test piece, a total of 5 points to test the resistivity, and take the average value of the resistivity results.

[0064] Excellent: Resistivity <0.3Ω*cm

[0065] Good: Resistivity is 0.3-0.5Ω*cm

[0066] Generally: resistivity is 0.5-0.7Ω*cm

[0067] Poor: resistivity>0.8Ω*cm

[0068]

Secondary battery cycle performance

[0069] Ten lithium-ion secondary batteries were made at 25°C, and one cycle was charged to 4.2V and discharged to 3V by a constant current method of 0.2C, and 200 cycles were performed. The ratio of the capacitance after 200 cycles to the average capacitance at the end of 5 cycles was calculated, and the discharge capacity retention rate = (average capacitance at the end of 200 cycles / average capacitance at the end of 5 cycles) * 100.

[0070] Excellent: Discharge capacity retention rate >80%

[0071] Good: Discharge capacity retention rate is 70-80%

[0072] Generally: discharge capacity retention rate is 60-70%

[0073] Poor: discharge capacity retention rate <60% Specific embodiments Example 1

[0074] Preparation of polymer: 20 parts of acrylic acid and solvent deionized water were added to the reactor, stirring and heating were started, and the temperature was raised to 60°C. 0.3 parts of initiator ammonium persulfate, 10 parts of methyl acrylate, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, 0.3 parts of initiator ammonium persulfate, 70 parts of acrylonitrile, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, the reaction was kept warm for 8 hours to prepare a polymer with an average molecular weight of 800,000.

[0075] Preparation of conductive adhesive composition for secondary battery: water, prepared polymer, and single-walled carbon nanotubes are added to the dispersion tank in sequence, the system temperature is controlled within 40°C, dispersed for 50 minutes, and then dispersed 25 times with a high-pressure homogenizer until the dispersion is uniform, and in-situ polymerization is carried out. The pH is adjusted to 5.5-6.5, and water is added to dilute to a carbon tube concentration of 0.2%, and dispersed again for 60 minutes. Add another batch of prepared polymers, keep the system temperature within 50°C, keep warm for 5h, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0076] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 65242 mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 38489 mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 29796 mPa·S. Example 2

[0077] Preparation of polymer: 40 parts of acrylic acid and solvent deionized water were added to the reactor, stirring and heating were started, and the temperature was raised to 70°C. 0.3 parts of initiator ammonium persulfate, 10 parts of acrylamide, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 80°C. After the addition was completed, 0.4 parts of initiator ammonium persulfate, 50 parts of acrylonitrile, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 80°C. After the addition was completed, the reaction was kept warm for 8 hours to prepare a polymer with an average molecular weight of 600,000.

[0078] Preparation of conductive adhesive composition for secondary battery: water, prepared polymer, and single-walled carbon nanotubes are added to the dispersion tank in sequence, the system temperature is controlled within 40°C, dispersed for 50 minutes, and then dispersed 25 times with a high-pressure homogenizer until the dispersion is uniform, and in-situ polymerization is carried out. The pH is adjusted to 5.5-6.5, and water is added to dilute to a carbon tube concentration of 0.2%, and dispersed again for 60 minutes. Add another batch of prepared polymers, keep the system temperature within 50°C, keep warm for 5h, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0079] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 50818 mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 29015mPa·S and the shear rate is 1.1S -1 The apparent viscosity is 20937 mPa·S. Example 3

[0080] Preparation of polymer: 30 parts of methyl acrylate and solvent deionized water were added to the reactor, stirring and heating were started, and the temperature was raised to 60°C. 0.5 parts of initiator ammonium persulfate, 20 parts of ethyl acrylate, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, 0.4 parts of initiator ammonium persulfate, 50 parts of methacrylamide, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, the reaction was kept warm for 8 hours to prepare a polymer with an average molecular weight of 400,000.

[0081] Preparation of conductive adhesive composition for secondary battery: Add water, prepared polymer and single-walled carbon nanotubes into the dispersion tank in sequence, control the system temperature within 30°C, disperse for 60 minutes, and then disperse 30 times with a high-pressure homogenizer until the dispersion is uniform, conduct in-situ polymerization, adjust the pH to 5.5-6.5, add water to dilute to a carbon tube concentration of 0.2%, and disperse again for 60 minutes. Add another batch of prepared polymers, keep the system temperature within 60°C, keep warm for 4 hours, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0082] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 35242 mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 21489 mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 16796 mPa·S. Example 4

[0083] Preparation of polymer: 60 parts of acrylic acid and solvent deionized water were added to the reactor, stirring and heating were started, and the temperature was raised to 60°C. 0.8 parts of initiator ammonium persulfate, 40 parts of acrylonitrile, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, the reaction was kept warm for 10 hours to prepare a polymer with an average molecular weight of 1 million.

[0084] Preparation of conductive adhesive composition for secondary battery: water, prepared polymer, and single-walled carbon nanotubes are added to the dispersion tank in sequence, the system temperature is controlled within 35°C, dispersed for 60 minutes, and then dispersed 30 times with a high-pressure homogenizer until the dispersion is uniform, and in-situ polymerization is carried out. The pH is adjusted to 5.5-6.5, and water is added to dilute to a carbon tube concentration of 0.2%, and dispersed again for 60 minutes. Add another batch of prepared polymers, keep the system temperature within 70°C, keep warm for 4 hours, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0085] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 89358 mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 66523mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 48769 mPa·S. Example 5

[0086] Preparation of polymer: 30 parts of acrylic acid and solvent deionized water were added to the reactor, stirring and heating were started, and the temperature was raised to 60°C. 0.3 parts of initiator ammonium persulfate, 35 parts of ethyl methacrylate, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, 0.2 parts of initiator ammonium persulfate, 35 parts of acrylamide, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, the reaction was kept warm for 8 hours to prepare a polymer with an average molecular weight of 600,000.

[0087] Preparation of conductive adhesive composition for secondary battery: Water, prepared polymer and single-walled carbon nanotubes are added into the dispersion tank in sequence, the system temperature is controlled within 30°C, dispersed for 60 minutes, and then dispersed 25 times with a high-pressure homogenizer until the dispersion is uniform, and in-situ polymerization is carried out, the pH is adjusted to 5.5-6.5, and water is added to dilute to a carbon tube concentration of 0.2%, and dispersed again for 40 minutes. Add another batch of prepared polymers, keep the system temperature within 60°C, keep warm for 5h, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0088] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 51436 mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 29817 mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 21310 mPa·S. Example 6

[0089] Preparation of polymer: 30 parts of methyl acrylate and solvent deionized water are added to the reactor, stirring and heating are started, and the temperature is raised to 60°C. 0.5 parts of initiator ammonium persulfate, 40 parts of ethyl methacrylate, and solvent deionized water are mixed and added dropwise to the reactor, and the reaction temperature is controlled at 80°C. After the addition is completed, 0.5 parts of initiator ammonium persulfate, 30 parts of acrylonitrile, and solvent deionized water are mixed and added dropwise to the reactor, and the reaction temperature is controlled at 80°C. After the addition is completed, the reaction is kept warm for 10 hours to prepare a polymer with an average molecular weight of 300,000.

[0090] Preparation of conductive adhesive composition for secondary battery: Add water, prepared polymer and single-walled carbon nanotubes into the dispersion tank in sequence, control the system temperature within 35°C, disperse for 60 minutes, and then disperse 25 times with a high-pressure homogenizer until the dispersion is uniform, conduct in-situ polymerization, adjust the pH to 5.5-6.5, add water to dilute to a carbon tube concentration of 0.2%, and disperse again for 40 minutes. Add another batch of prepared polymers, keep the system temperature within 50°C, keep warm for 7 hours, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0091] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 78065mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 53901mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 45212 mPa·S. Example 7

[0092] Preparation of polymer: 60 parts of acrylic acid and solvent deionized water were added to the reactor, stirring and heating were started, and the temperature was raised to 60°C. 0.3 parts of initiator ammonium persulfate, 15 parts of ethyl methacrylate, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, 0.3 parts of initiator ammonium persulfate, 25 parts of acrylonitrile, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 80°C. After the addition was completed, the reaction was kept warm for 10 hours to prepare a polymer with an average molecular weight of 500,000.

[0093] Preparation of conductive adhesive composition for secondary battery: water, prepared polymer, and single-walled carbon nanotubes are added to the dispersion tank in sequence, the system temperature is controlled within 30°C, dispersed for 60 minutes, and then dispersed 25 times with a high-pressure homogenizer until the dispersion is uniform, and in-situ polymerization is carried out. The pH is adjusted to 5.5-6.5, and water is added to dilute to a carbon tube concentration of 0.2%, and dispersed again for 50 minutes. Add another batch of prepared polymers, keep the system temperature within 60°C, keep warm for 6 hours, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0094] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 45780 mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 28903mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 19875 mPa·S. Example 8

[0095] Preparation of polymer: 60 parts of methyl acrylate and deionized water solvent were added to the reactor, stirring and heating were started, and the temperature was raised to 60°C. 0.4 parts of initiator ammonium persulfate, 20 parts of ethyl acrylate, and deionized water solvent were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, 0.4 parts of initiator ammonium persulfate, 20 parts of sodium allyl sulfonate, and deionized water solvent were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 60°C. After the addition was completed, the reaction was kept warm for 7 hours to prepare a polymer with an average molecular weight of 400,000.

[0096] Preparation of conductive adhesive composition for secondary battery: Add water, prepared polymer and single-walled carbon nanotubes into the dispersion tank in sequence, control the system temperature within 30°C, disperse for 50 minutes, and then disperse 30 times with a high-pressure homogenizer until the dispersion is uniform, conduct in-situ polymerization, adjust the pH to 5.5-6.5, add water to dilute to a carbon tube concentration of 0.2%, and disperse again for 40 minutes. Add another batch of prepared polymers, keep the system temperature within 50°C, keep warm for 5h, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0097] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 72923 mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 58392mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 47332 mPa·S. Example 9

[0098] Polymer preparation: Add 60 parts of acrylic acid and solvent deionized water into the reactor, start stirring and heating, and raise the temperature to 60°C. Mix 0.3 parts of initiator ammonium persulfate, 10 parts of ethyl acrylate, and solvent deionized water and add them dropwise to the reactor, and control the reaction temperature to 70°C. After the addition is completed, mix 0.2 parts of initiator ammonium persulfate, 15 parts of methyl acrylate, and solvent deionized water and add them dropwise to the reactor. After the addition is completed, mix 0.2 parts of initiator ammonium persulfate, 15 parts of acrylamide, and solvent deionized water and add them dropwise to the reactor, and control the reaction temperature to 60°C. After the addition is completed, keep the reaction warm for 6 hours to prepare a polymer with an average molecular weight of 800,000.

[0099] Preparation of conductive adhesive composition for secondary battery: water, prepared polymer, and single-walled carbon nanotubes are added to the dispersion tank in sequence, the system temperature is controlled within 40°C, dispersed for 50 minutes, and then dispersed 30 times with a high-pressure homogenizer until it is evenly dispersed, and in-situ polymerization is carried out. The pH is adjusted to 5.5-6.5, and water is added to dilute to a carbon tube concentration of 0.2%, and dispersed again for 40 minutes. Add another batch of prepared polymers, keep the system temperature within 50°C, keep warm for 7 hours, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0100] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 97365mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 77997mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 60052 mPa·S.

[0101] Comparative Example 1

[0102] Polymer preparation: 60 parts of acrylonitrile and deionized water solvent were added to the reactor, stirring and heating were started, and the temperature was raised to 60°C. 1 part of initiator ammonium persulfate, 40 parts of acrylamide, and deionized water solvent were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, the reaction was kept warm for 6 hours to prepare a polymer with an average molecular weight of 150,000.

[0103] Preparation of conductive adhesive composition for secondary battery: Add water, prepared polymer and single-walled carbon nanotubes into the dispersion tank in sequence, control the system temperature within 30°C, disperse for 60 minutes, and then disperse 25 times with a high-pressure homogenizer until the dispersion is uniform, conduct in-situ polymerization, adjust the pH to 5.5-6.5, add water to dilute to a carbon tube concentration of 0.2%, and disperse again for 60 minutes. Add another batch of prepared polymers, keep the system temperature within 60°C, keep warm for 8 hours, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0104] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 26803 mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 18076 mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 11978 mPa·S.

[0105] Comparative Example 2

[0106] Preparation of polymer: 60 parts of acrylic acid and solvent deionized water were added to the reactor, stirring and heating were started, and the temperature was raised to 60°C. 0.3 parts of initiator ammonium persulfate, 35 parts of methyl acrylate, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, 0.1 parts of initiator ammonium persulfate, 5 parts of acrylamide, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, the reaction was kept warm for 6 hours to prepare a polymer with an average molecular weight of 1.5 million.

[0107] Preparation of conductive adhesive composition for secondary battery: Add water, prepared polymer and single-walled carbon nanotubes into the dispersion tank in sequence, control the system temperature within 40°C, disperse for 60 minutes, and then disperse 25 times with a high-pressure homogenizer until the dispersion is uniform, conduct in-situ polymerization, adjust the pH to 5.5-6.5, add water to dilute to a carbon tube concentration of 0.2%, and disperse again for 60 minutes. Add another batch of prepared polymers, keep the system temperature within 70°C, keep warm for 6 hours, adjust the pH to 7-8, and filter out the insoluble matter to obtain a conductive adhesive composition for secondary battery.

[0108] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 128748 mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 99783mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 66432 mPa·S.

[0109] Comparative Example 3

[0110] Preparation of polymer: 50 parts of acrylonitrile and solvent deionized water were added to the reactor, stirring and heating were started, and the temperature was raised to 60°C. 0.2 parts of initiator ammonium persulfate, 10 parts of acrylic acid, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, 0.2 parts of initiator ammonium persulfate, 40 parts of sodium allyl sulfonate, and solvent deionized water were mixed and added dropwise to the reactor, and the reaction temperature was controlled at 70°C. After the addition was completed, the reaction was kept warm for 6 hours to prepare a polymer with an average molecular weight of 1.2 million.

[0111] Preparation of conductive adhesive composition for secondary battery: water, prepared polymer and single-walled carbon nanotubes are added into the dispersion tank in sequence, the system temperature is controlled within 40°C, dispersed for 60 minutes, pH adjusted to 5.5-6.5, diluted with water to a carbon tube concentration of 0.2%, and dispersed again for 40 minutes. Another batch of prepared polymer is added, the system temperature is maintained within 40°C, kept warm for 4 hours, pH adjusted to 7-8, and insoluble matter is filtered to obtain a conductive adhesive composition for secondary battery.

[0112] The rheological properties of the conductive adhesive composition for secondary batteries were tested at a shear rate of 0.2S -1 When the apparent viscosity is 101563mPa·S, the shear rate is 0.6S -1 The apparent viscosity is 80215mPa·S and the shear rate is 1.1S -1 The apparent viscosity at this time is 68531 mPa·S.

[0113] Table 1 Test results

[0114]

[0115] Experimental results analysis:

[0116] 1. Comparative Example 1 and Examples 1 to 9 show that the conductive adhesive composition for secondary batteries has a shear rate of 0.2S at 25°C. -1 When the apparent viscosity is 30000-100000mPa·S; the shear rate is 0.6S -1 When the apparent viscosity is 20000-50000mPa·S; the shear rate is 1.1S -1 When the apparent viscosity is 15000-40000 mPa·S and the polymer contains 30% by weight or more and 85% by weight of acrylic acid (ester) monomer units, the prepared slurry has better stability, stronger electrode peeling strength and lower electrode resistance, thereby effectively improving the cycle performance of the secondary battery.

[0117] 2. Comparative Example 2 and Examples 1 to 9 show that the conductive adhesive composition for secondary batteries has a shear rate of 0.2S at 25°C. -1 When the apparent viscosity is 30000-100000mPa·S; the shear rate is 0.6S -1 When the apparent viscosity is 20000-50000mPa·S; the shear rate is 1.1S -1 When the apparent viscosity is 15000-40000 mPa·S and the weight-average molecular weight of the polymer is more than 200,000 and less than 1,000,000, the prepared slurry has better stability, stronger electrode peeling strength and lower electrode resistance, thereby effectively improving the cycle performance of the secondary battery.

[0118] 3. Comparative Example 3 and Examples 1 to 9 show that the conductive adhesive composition for secondary batteries has a shear rate of 0.2S at 25°C. -1 When the apparent viscosity is 30000-100000mPa·S; the shear rate is 0.6S -1 When the apparent viscosity is 20000-50000mPa·S; the shear rate is 1.1S -1When the apparent viscosity is 15000-40000mPa·S, the polymer and the conductive agent are subjected to an in-situ polymerization process to form a conductive polymer. The prepared slurry has better stability, stronger electrode peeling strength, and lower electrode resistance, thereby effectively improving the cycle performance of the secondary battery.

[0119] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A conductive adhesive composition for a secondary battery, characterized in that: Contains solvent, polymer and conductive agent; Wherein, the rheological properties of the conductive adhesive composition for secondary batteries are as follows: At 25°C, the shear rate is 0.2S -1 When the apparent viscosity is 30000-100000mPa·S; the shear rate is 0.6S -1 When the apparent viscosity is 20000-50000mPa·S; the shear rate is 1.1S -1 hour, The apparent viscosity is 15000-40000mPa·S, The polymer monomer is selected from any combination of acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, butyl methacrylate, allyl methacrylate, glycidyl methacrylate, dipropylene adipate, acrylamide, methacrylamide, N-hydroxymethyl acrylamide, methylene bisacrylamide, acrylonitrile, methacrylonitrile, allyl sulfonate, and propylene sulfonate. The polymer contains 30 to 85 weight percent of acrylic acid (ester) monomer units.

2. The conductive adhesive composition for secondary batteries according to claim 1, wherein The polymer system is prepared by free radical polymerization of polymer monomers.

3. The conductive adhesive composition for secondary batteries according to claim 1, wherein The solvent comprises 80-100 parts of water and 0-20 parts of an organic solvent in terms of weight ratio, and the organic solvent is selected from a combination of one or more of ethanol, isopropanol, n-butanol, and acetonitrile.

4. The conductive adhesive composition for secondary batteries according to claim 1, wherein The polymer has a weight average molecular weight of 200,000 to 1,000,000.

5. The conductive adhesive composition for secondary batteries according to claim 1, wherein The conductive agent is a combination of one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, carbon black, graphite, and carbon fiber.

6. The conductive adhesive composition for secondary batteries according to claim 5, wherein The conductive agent is single-walled carbon nanotube.

7. The conductive adhesive composition for secondary batteries according to claim 1, wherein The polymer and the conductive agent are polymerized in situ to form a conductive macromolecule. 8 . A negative electrode slurry for a lithium ion battery, comprising an electrode active material and the conductive binder composition for a secondary battery according to claim 1 .

9. A negative electrode sheet for a lithium-ion secondary battery, characterized in that: The invention comprises a current collector and the negative electrode slurry of the lithium ion battery according to claim 8. 10 . A lithium ion secondary battery comprising the negative electrode sheet for a lithium ion secondary battery according to claim 9 .

Citation Information

Patent Citations

  • Shear thickening graphene composite conductive paste and preparation method thereof

    CN115116649A